Early detection to improve outcome in people with undiagnosed psoriatic arthritis: the PROMPT research programme including RCT - Neil McHugh; Laura Bojke; Mel Brooke Turfrey; Rachel Charlton; Myka Ransom; Laura C Coates; Howard Collier; Claire Davies; Emma Dures; Philip Helliwell; Jana James; Anya Lissina; et al. (Programme Grants for Applied Research)
Background Longitudinal observational studies suggest that patients who present early to secondary care with psoriatic arthritis have a better outcome. Outcome needs to be measured including domains important to patients. Objectives To identify disease activity and impact outcomes important to patients with psoriatic arthritis in comparison to existing ones (Patient-Reported Outcome Measurement Study). To assess the validity of new measures of disease activity in psoriatic arthritis derived from patient engagement (ASSESSment of modified composite disease measures study). To explore patients’ experiences of diagnosis in psoriatic arthritis? (Experiences of screening and diaGnosis from the perspective of pAtients with PSoriasis and psoriatic arthritis study). To identify modifiable risk factors for the development of psoriatic arthritis using the Clinical Practice Research Datalink (EPIdemiology of psoriatiC arthritis study). To compare the performance of screening tools for detecting undiagnosed psoriatic arthritis (COMparison of Psoriatic Arthritis scREening tools study). To investigate the clinical effectiveness (Total bUrDen Of psoRiasis trial) and cost-effectiveness (COSt of screening for Psoriatic Arthritis study) of detecting undiagnosed psoriatic arthritis. Design and methods Mixed methods using data from patient focus groups, a multicentre cohort study, primary care health records (Clinical Practice Research Datalink) and a prospective randomised clinical trial (Total bUrDen Of psoRiasis trial, COMparison of Psoriatic Arthritis scREening tools study, COSt of screening for Psoriatic Arthritis study). Setting and participants Focus groups and cohort studies of 221 patients with psoriatic arthritis including newly diagnosed cases (Patient-Reported Outcome Measurement Study, ASSESSment of modified composite disease measures study, experiences of screening and diaGnosis from the perspective of pAtients with PSoriasis and psoriatic arthritis study) and 2225 patients with psoriasis from primary care not known to have psoriatic arthritis from 135 randomised general practices (COMparison of Psoriatic Arthritis scREening tools study, Total bUrDen Of psoRiasis trial randomised clinical trial, COSt of screening for Psoriatic Arthritis study). Intervention Randomised controlled trial comparing the early identification of psoriatic arthritis by annual rheumatological assessment (enhanced surveillance) in people with psoriasis identified in primary care (n = 1123) with standard care (n = 1102). Participants with suspected inflammatory arthritis were referred to the local rheumatology clinic for an assessment of psoriatic arthritis (enhanced surveillance arm: at baseline, 12 and 24 months; standard care arm: at 24 months). Data sources Cohort studies of incident psoriasis (n = 90,189) or psoriatic arthritis (n = 6783) patients from the Clinical Practice Research Datalink (EPIdemiology of psoriatiC arthritis study). Cost-effective analysis using data collected in Total bUrDen Of psoRiasis trial. Modelling exercise to extrapolate screening performance from Total bUrDen Of psoRiasis trial to long-term costs and quality-adjusted life-years (COSt of screening for Psoriatic Arthritis study). Main outcome measure In Total bUrDen Of psoRiasis trial the primary outcome was the Health Assessment Questionnaire Disability Index at 24 months post registration in participants diagnosed with psoriatic arthritis. Results Patient-Reported Outcome Measurement Study: Patients rated pain and fatigue as the most important outcomes when receiving treatment for psoriatic arthritis. ASSESSment of modified composite disease measures study: Shortened versions of visual analogue scales performed well in detecting treatment change and responsiveness over 6 months. Experiences of screening and diaGnosis from the perspective of pAtients with PSoriasis and psoriatic arthritis study: Missed opportunities for psoriatic arthritis diagnosis has implications for well-being including mental health, and there is a need for provision of psychological support and self-management guidance. Screening for psoriatic arthritis was generally regarded as a positive experience. EPIdemiology of psoriatiC arthritis study: Bayesian networks identified clusters of symptoms that can accurately predict the development of psoriatic arthritis (area under the curve 0.73, 95% CI 0.70 to 0.75). Obesity is a modifiable lifestyle factor that increases the risk of developing psoriatic arthritis and diminishes linearly over a 10-year period with a reduction in body mass index. Diabetes, cardiovascular disease, uveitis and Crohn’s disease are associated with psoriatic arthritis and may appear early in the disease course. COMparison of Psoriatic Arthritis scREening tools study: The Psoriasis Epidemiology Screening Tool questionnaire remains the preferred screening tool, given its simplicity with no significant differences in performance (sensitivity: 0.625, specificity: 0.757, area under the curve 0.787) compared to COmparisoN of ThreE Screening Tools to detect psoriatic arthritis in patients with psoriasis. Total bUrDen Of psoRiasis trial: The primary analysis population consisted of 87 participants with a positive diagnosis of psoriatic arthritis: 64 in enhanced surveillance, 23 in standard care (overall mean Health Assessment Questionnaire Disability Index score at 24 months was 0.45). The adjusted odds ratio for achieving a Health Assessment Questionnaire Disability Index score of 0 at 24 months post registration in enhanced surveillance compared to standard care was 0.64 (95% CI 0.17 to 2.38), and the adjusted odds ratio of achieving a higher (non-zero) Health Assessment Questionnaire Disability Index score at 24 months post registration in enhanced surveillance relative to standard care arm was 1.12 (95% CI 0.67 to 1.86), indicating no evidence of a difference between the two treatment groups (p = 0.6612). COSt of screening for Psoriatic Arthritis study: The within-trial cost-effectiveness analysis suggests that enhanced surveillance may be associated with higher mean quality-adjusted life-years, although the difference was very small (+0.002, 95% CI –0.03 to 0.03), and lower mean costs (−£120.54, 95% CI –£540.57 to £288.99). Using the cost-effectiveness model based on the sensitivity, specificity and the psoriatic arthritis incidence from the Total bUrDen Of psoRiasis trial, Psoriasis Epidemiology Screening Tool is the most expensive and has the highest lifetime quality-adjusted life-years with an incremental cost-effectiveness ratio of £14,964 per additional quality-adjusted life-year compared to CONTEST, CONTESTjt and no screening using a lifetime time horizon. Limitations The Total bUrDen Of psoRiasis trial was underpowered due to a lower proportion of patients developing psoriatic arthritis than expected (87 compared to 148) and disruption to follow-up due to the coronavirus pandemic. COSt of screening for Psoriatic Arthritis study analyses were limited by the extent of missing data. Conclusion The benefit of early detection of psoriatic arthritis in a primary care psoriasis population remains unproven. Surveillance for undiagnosed psoriatic arthritis generally detects mild cases as measured by physical function. Patients rate pain and fatigue as the most important outcomes. Future work Five-year follow-up of Total bUrDen Of psoRiasis trial participants to investigate longer-term benefits of earlier diagnosis comparing treatment arms and to assess risk factors for psoriatic arthritis development is underway. Trial registration This trial is registered as Current Controlled Trials ISRCTN38877516. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Programme Grants for Applied Research programme (NIHR award ref: RP-PG-1212-20007) and is published in full in Programme Grants for Applied Research; Vol. 13, No. 6. See the NIHR Funding and Awards website for further award information. Plain language summary Psoriasis is a chronic skin condition affecting about 2% of the population often causing an itchy scaly rash, sometimes sore and affecting any part of the body surface. We know that about 20% of people with psoriasis develop a form of joint inflammation called psoriatic arthritis, and that in most cases the skin condition comes before the arthritis. We do not really know whether detecting cases of arthritis earlier by screening for it in people with psoriasis leads to a better outlook. Also, we need better ways of measuring that outlook that are most meaningful to patients. Our Total bUrDen Of psoRiasis trial investigated whether screening people for psoriatic arthritis was more effective than not screening. Total bUrDen Of psoRiasis trial was run over 2 years and recruited 2225 people with psoriasis from general practitioner practices in United Kingdom. Our trial did not show any significant difference between the groups, possibly because we ended up with fewer people developing psoriatic arthritis than expected. However, 86% of the 2225 Total bUrDen Of psoRiasis trial participants agreed to be approached for future research, providing opportunities to better understand who is most at risk of psoriatic arthritis and how best to support them. From psoriatic arthritis patient focus groups, we learnt that the two most important symptoms were pain and fatigue, issues which had not been regarded as important to measure in previous clinical trials. Patients told us that they wanted support to understand the condition, make decisions about treatments, find ways to cope with the emotional challenges that they faced and make changes to their lifestyles to help with their arthritis. From our work using anonymised United Kingdom primary care records, we found that patients with psoriatic arthritis have increased chances of being overweight and having complications such as diabetes and heart disease, reinforcing the need for better educational packages in current healthcare pathways. Scientific summary Background Psoriatic arthritis (PsA) affects approximately one in four people with pre-existing psoriasis. Screening patients with psoriasis for PsA in primary care/dermatology clinics has revealed a high prevalence (14–29%) of undiagnosed disease. Preliminary studies, including our own, have identified a significant need for the earlier diagnosis of PsA. There is some evidence that delay in diagnosis results in unfavourable outcomes with increased health costs and work disability. There is solid evidence that early treatment lessens long-term disease burden in rheumatoid arthritis, but this has not yet been shown for PsA. As psoriasis precedes PsA in ~70% of cases, there is a unique opportunity to develop an optimal screening strategy to apply to people with psoriasis and determine whether early diagnosis of PsA is both clinically effective and cost-effective. From studies we have led we know that outcome measures for PsA need to be refined to encompass domains that people with PsA have identified as important, such as fatigue, pain, skin disease and work disability. Aims and objectives The overall aim was to provide an evidence-based framework for recommendations on an effective and acceptable screening strategy for the early identification of PsA in people with psoriasis in primary care and their subsequent management. We also needed to ensure that the measures of outcome to assess the effectiveness of early detection encompassed aspects of early disease that were meaningful and important to patients. Key questions were as follows (with the relevant study to address the question) Which patient-reported outcome measures are the most appropriate to incorporate in future composite outcome assessment instruments for PsA? [Patient-Reported Outcome Measurement Study (PROMS)] Do modified composite outcome instruments for PsA accurately reflect changes important to patients and clinicians? [ASSESSment of modified composite disease measures study (ASSESS)] What barriers contribute to delay in diagnosis in PsA? [Experiences of screening and diaGnosis from the perspective of pAtients with PSoriasis and psoriatic arthritis study (GAPS)] What is the burden of disease, evolution of symptoms and lifestyle risk in people with psoriasis in primary care who develop PsA? [EPIdemiology of psoriatiC arthritis study (EPIC)] What is the best screening questionnaire to identify PsA in people with psoriasis in primary care? [COMparison of Psoriatic Arthritis scREening tools study (COMPARE)] Does early detection of PsA result in improved measures of outcome? [Total bUrDen Of psoRiasis trial (TUDOR)] What is the cost-effectiveness of screening people with psoriasis for PsA and, if appropriate, early intervention? [COSt of screening for Psoriatic Arthritis study (COSPA)] Programme of work and findings Patient-Reported Outcome Measurement Study Our aim was to identify the outcomes that are important to patients with PsA and to compare them to existing composite measures and the Outcome Measures in Rheumatology (OMERACT) core set of domains internationally recommended for the assessment of PsA. We conducted the study in five phases, using qualitative, consensus and reviewing methods. Through 8 focus groups (41 patients), we identified over 60 outcomes from treatments that are important to patients, some of which are not commonly measured. From 7 nominal group technique meetings (32 patients), the highest ranked outcomes which patients wished to see from treatment were pain with 93 points (20.0%), fatigue 62 (13.3%), physical fitness 33 (7.1%), halting/slowing damage 32 (6.9%) and quality of life (QoL)/well-being 29 (6.2%). Mapping the high-priority outcomes to existing composite measures for PsA demonstrated that no single measure adequately captured all these outcomes or covered the recommended OMERACT PsA core domain set. The two highest ranked outcomes (pain and fatigue) were poorly represented in existing composite measures. The findings from PROMS informed the outcome measures collected in ASSESS and the modifications and shortening of existing composite measures. ASSESSment of modified composite disease measures study The ASSESS study aimed to improve outcome measurement in PsA through the incorporation of the patient perspective into existing composite measures of disease activity, develop feasible composite measures for clinical practice and validate a flare questionnaire. Clinical and patient-reported outcome measures were assessed in 139 patients with PsA at three consecutive follow-up visits in a UK multicentre observational study. A pain visual analogue scale (VAS) and Functional Assessment of Chronic Illness Therapy-Fatigue instrument (chosen from PROMS) were added as modifications to the Composite Psoriatic Disease Activity Index (CPDAI) and the GRAppa Composite Exercise (GRACE) composite measures. The VAS3 (Physician global VAS, Patient global and skin VAS) or VAS4 (Physician global VAS, Patient pain, joint and skin VAS) were tested as shortened composite measures. The addition of pain and fatigue to CPDAI/GRACE did not enhance responsiveness or their ability to detect disease status in terms of requiring treatment escalation. Shortening the GRACE to VAS scores alone enhanced the ability to detect status and responsiveness and had the best performance characteristics of the tested composite measures. The flare questionnaire had external validity both in terms of composite disease activity and overall patient opinion of the state of their condition. Experiences of screening and diaGnosis from the perspective of pAtients with PSoriasis and psoriatic arthritis study We collected evidence on patients’ experiences of two types of care provision: current health care and screening as part of the TUDOR trial. We had two main study aims: To understand experiences of diagnosis in the current healthcare context from the perspective of patients newly diagnosed with PsA. To understand experiences of screening from the perspective of patients with psoriasis who were recruited to the screening arm in the TUDOR trial. We conducted the study in two phases. In both phases, we used a qualitative study design and collected data through one-to-one interviews, which we analysed thematically. In phase 1, 15 newly diagnosed patients (< 24 months) with PsA recruited from 3 hospital sites participated. We identified two main themes that represented the data: symptom onset to specialist care, and diagnosis as a turning point. We found that by the time participants received their diagnosis, they were already dealing with functional limitations and were highly distressed and anxious. In phase 2, 24 patients with psoriasis recruited from 2 hospital sites participated, after they had completed their outcomes in the TUDOR trial. We identified three main themes: living with psoriasis and PsA, effects of screening on patients and increased knowledge and self-management. We found that screening was acceptable to patients and perceived as beneficial both among those who did and did not receive a diagnosis of PsA. EPIdemiology of psoriatiC arthritis study The EPIC study aimed to describe the evolution of musculoskeletal symptoms in people with psoriasis and their comorbidities, and investigate the role of smoking, alcohol and obesity in PsA development. This study used data from the UK’s Clinical Practice Research Datalink, including 90,187 incident cases of psoriasis and 6783 incident cases of PsA. Using Bayesian networks (BNs), direct relationships were identified between gender, body mass index (BMI), arthralgia, finger pain, fatigue, hand pain, hip pain, knee pain, swelling, back pain, myalgia and PsA. The best BN, using more site-specific musculoskeletal symptom subgroups, was 76% accurate in predicting the development of PsA and had an area under the receiver operating characteristic curve (AUC) of 0.73 [95% confidence interval (CI) 0.70 to 0.75]. Patients with PsA had a significant increase in risk of developing type 2 diabetes, uveitis, Crohn’s disease, and osteoarthritis, but not ulcerative colitis, when compared to general population and psoriasis controls. For cardiovascular disease, significant increases in risk were observed in PsA patients compared to the general population but not to psoriasis controls. Body mass indexes of 25.0–29.9, 30.0–34.9 and ≥ 35.0 kg/m2 were significantly associated with an increased risk of developing PsA compared with BMIs < 25.0 kg/m2 adjusted odds ratios (OR; 95% CI) 1.79 (1.46 to 2.19), 2.10 (1.67 to 2.63) and 2.68 (2.09 to 3.43), respectively. Reducing BMI over a 10-year period (linearly) was associated with a reduction in the risk of developing PsA compared with BMI remaining constant over the same period. Increased risks of developing PsA were associated with moderate drinking but not with former or heavy drinking or with current or past smoking status. These results have important implications for surveillance and management of important comorbidities in early PsA. Reducing weight is associated with a lower risk of developing PsA. BN models may be a useful method to identify clusters of symptoms that predict PsA with reasonable accuracy. COMparison of Psoriatic Arthritis scREening tools The Psoriasis Epidemiology Screening Tool (PEST) was previously recommended by National Institute for Health and Care Excellence, although there were concerns about its performance in certain PsA subtypes. Revised screening tools (CONTEST and CONTESTjt), from the COmparisoN of ThreE Screening Tools (CONTEST) study, incorporating the most discriminatory items from PEST and other relevant questionnaires, were then designed. COMparison of Psoriatic Arthritis scREening tools study investigated the best screening questionnaire for use in routine primary care to identify undiagnosed PsA in 791 people with psoriasis from the TUDOR trial. The performances of PEST and CONTESTjt screening tools were compared in terms of estimates of sensitivity, specificity, positive and negative predictive values, and AUC. Analogous exploratory analyses were undertaken with the CONTEST questionnaire. The study found that using prespecified thresholds, PEST had higher estimates for sensitivity (0.625, 95% CI 0.482 to 0.749) than CONTESTjt (0.542, 95% CI 0.401 to 0.676), whereas CONTESTjt had higher estimates for specificity (0.834, 95% CI 0.805 to 0.859) than PEST (0.757, 95% CI 0.724 to 0.787). The sensitivity and specificity estimates for CONTEST lay between those of PEST and CONTESTjt (sensitivity 0.604, 95% CI 0.461 to 0.731; specificity 0.768, 95% CI 0.736 to 0.798). As an overall measure of screening performance, PEST had the highest estimate for AUC (0.787, 95% CI 0.727 to 0.847) and CONTESTjt the lowest (0.765, 95% CI 0.695 to 0.835), with values for CONTEST appearing in between (0.768, 95% CI 0.699 to 0.837). However, there was no evidence of a difference in AUC estimates between PEST and the other questionnaires. Therefore, PEST remains the preferred screening tool due to its simplicity and performance. Total bUrDen Of psoRiasis trial Intervention Two-arm parallel-group cluster randomised controlled trial of the early identification of PsA by annual rheumatological assessment [termed enhanced surveillance (ES)] in people with psoriasis identified in primary care versus standard care (SC). Participants with suspected inflammatory arthritis were referred to the local rheumatology clinic for an assessment of PsA (ES arm: at baseline, 12 and 24 months; SC arm: at 24 months). The primary objective of TUDOR was to determine whether the early detection of undiagnosed PsA in people with psoriasis by ES compared to SC improves outcome in physical function at 24 months post registration. Secondary objectives were to compare disease and impact of disease between people diagnosed with PsA in the ES and SC arms at 24 months post registration. A total of 2225 participants with psoriasis were registered, corresponding to 1123 allocated to ES and 1102 to SC. However, due to the lower proportion of participants with undiagnosed PsA than assumed in the original trial design, only 87 participants diagnosed with PsA, rather than a predicted target of 148, were included in the primary analysis population. The adjusted odds of achieving a Health Assessment Questionnaire-Disability Index (HAQ-DI) score of 0 at 24 months post registration were 36% lower in the ES arm compared to the SC arm [OR 0.64, 95% CI (0.17 to 2.38)], suggesting a more favourable outcome in the SC arm. However, there was no evidence of a difference between the two treatment groups (p = 0.5075). Moreover, the adjusted odds of achieving a higher (non-zero) HAQ-DI score at 24 months post registration were 12% higher in the ES arm compared to the SC arm [OR 1.12 (95% CI 0.67 to 1.86)], suggesting that physical function at 24 months was observed to be lower in ES arm. However, again there was no evidence of a difference between the two treatment groups. There is high variability on the impact of the disease between participants over time, although the impact is generally low in this group of participants with an ‘early’ diagnosis of PsA. Moreover, the overall Psoriatic Arthritis Disease Activity Score and component scores over time post PsA diagnosis show high variability in PsA disease activity between participants over time. No adverse events were reported during the trial. COSt of screening for Psoriatic Arthritis study The economic analysis constituted a within-trial cost-effectiveness analysis and economic modelling using screening performance from TUDOR. Within-trial analysis The within-trial analysis (from 960 participants with complete data) generated a cost per quality-adjusted life-year (QALY) for ES versus standard practice over 2 years. Resource use data collected in TUDOR were combined with national unit costs to estimate the total costs of screening and SC. Productivity was measured using Work Productivity and Activity Impairment – General Health. Multiple imputation methods were used to impute missing data for costs and QALYs. ES was associated with higher mean QALYs (+0.002, 95% CI –0.03 to 0.03) and lower mean costs (−£120.54, 95% CI –£540.57 to £288.99). ES dominated SC on the basis of the imputed data set. Modelling analysis To estimate the long-term consequences and cost-effectiveness of screening for PsA, a hypothetical cohort of 45-year-old patients with mild psoriasis and without PsA was modelled. Annual progression of PsA was measured by the HAQ-DI scores. The main analysis used a 40-year time horizon with annual cycles. Annual incidence of PsA from TUDOR was 2.74%. Base-case analysis shows that no screening is the least expensive option but results in the lowest QALYs. The PEST screening test is the costliest but had the highest probability, 0.39, of being cost-effective at a threshold of £30,000 per QALY. Up to a cost-effectiveness threshold of £11,500 per QALY, ‘no screening’ is most likely to be the cost-effective option, at a cost-effectiveness threshold between £11,500 per QALY and £18,200 per QALY, the CONTESTjt is most likely to be the cost-effective option and at a cost-effectiveness threshold of greater than or equal to £18,200 per QALY, PEST is most likely to be the cost-effective option. Conclusions Implications for practice The PEST instrument remains an appropriate screening tool for use in identifying PsA in primary care. Receiving a diagnosis of PsA comes with a need for psychological and educational support. Pain and fatigue are important outcomes to patients with PsA that need measurement and VASs are reliable and practical for capturing disease activity. Obesity is an important modifiable risk factor associated with the development of PsA. Limitations The TUDOR trial was underpowered for demonstrating the pre-specified treatment effect, and the within-trial cost-effectiveness analysis (COSPA) was limited by the extent of missing data. Future research Priorities are extended follow-up of TUDOR participants to investigate clinical effectiveness and cost-effectiveness of screening for PsA, further validation of VAS in routine clinical practice, defining a comprehensive risk factor for development of PsA, and selecting the most appropriate psoriatic population for screening. Trial registration This trial is registered as Current Controlled Trials ISRCTN38877516. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Programme Grants for Applied Research programme (NIHR award ref: RP-PG-1212-20007) and is published in full in Programme Grants for Applied Research; Vol. 13, No. 6. See the NIHR Funding and Awards website for further award information.